RANCANG BANGUN SISTEM PENJUALAN KUE ONLINE BERBASIS WEB DENGAN PENDEKATAN FEATURE DRIVEN DEVELOPMENT (FDD) ELLUFFI HOME BAKERY - Putri, Yunda; Sokibi, Petrus; Norham, Linda (Program Studi Informatika Fakultas Teknik Universitas Janabadra, 2025)
The development of information technology encourages business owners to utilize web-based systems to improve business effectiveness. Elluffi Home Bakery previously relied on conventional ordering methods through WhatsApp, which caused several issues such as unstructured order data and limitations in transaction management. This study aims to design and develop a web-based online cake sales system using the Feature Driven Development (FDD) method. The FDD method consists of five stages, namely Develop an Overall Model, Build a Feature List, Plan by Feature, Design by Feature, and Build by Feature. The system was developed with key features such as product management, shopping cart, ordering, transaction history, sales reports, and user authentication. Testing was carried out using User Acceptance Testing (UAT). Based on the results, it can be concluded that the developed web-based online cake sales system is able to simplify the transaction process, document order data in a more structured manner, and improve business management efficiency. Therefore, this system can assist Elluffi Home Bakery in expanding marketing reach and increasing competitiveness in the digital era.